Gênese e evolução de sistemas pedológicos em unidades de paisagem do município de Marechal Cândido Rondon-PR - Magalhães, Vanderlei Leopold (2013)
In order to prove the hypothesis that pedological systems, geomorphological compartments, called Marechal, Margarida and Porto Mendes Plateau, from Marechal Cândido Rondon - West of Paraná were in different stages of evolution, in this study we aimed to understand the genesis and transformations in these three predominant soil landscape units, considered the most representative of the municipality. For this purpose, the methodology of Structural Analysis Coverage Pedologic was used for recognition of the organization and operation of these pedological systems, with polls and trenches in the main sectors of the topographical aspects, for macro and micromorphological and physical-hydric characterization of diagnostic horizons. The unit of Marechal Plateau, consisted by eutroferric red latosol on top and distroferric red latosolic nitosol from the average slope, side transformations evidence indicating the deconstruction of the Bw horizon over the advancing B nitic on the hieghst sectors on the slope, which shows a pedomorphologic imbalance. The landscape unit of Margarida is constituted by eutroferric red latosol leads to the inference of a possible transformation of the Bw horizon in polyhedral structures, assuming B nitic features. In the landscape unit of Porto Mendes it was possible to identify a podologic soil cover composed by eutroferric red latosol apparently in equilibrium to the current conditions. Micromorphological data, particularly the organization of microstructures and temporal system, also contributed to the understanding of the physical behavior of hydro-pedological systems. These results demonstrated the occurrence of traces of two flattened surfaces (Pd0 and Pd1), from which the current strands were modeled by drain slot, and a pediments zone and / or staggered heights and ramps that make the transition between them, which allows us to identify that the units of Porto Mendes and Margarida are connected by the processes and products of preparing this waterfront pediplain. The pediplained Pd0 level, which shot the hilltops drives from Porto Mendes, extends the unit of Margarida, along the valleys, corresponding to pediments, currently also carved, spurs topographically higher. The spurs, in turn, the tops appear relatively narrow spread (in steps) until it reaches the edge of the Marechal plateau. The stagger of these spurs tops originated probably in dissection ramp connection between Pd1 and Pd2. Disparities in steps or levels can be structural and not just morphoclimatic, since it is a relief to evolve over rocks originating from volcanic flows. The alternation of massive levels thicker basalt levels thinner or vesicular and amigdaloidal can produce this staggering when dissected. In summary, the three landscape units have their own characteristics, mainly generated by regional geomorphological evolution, whose evolution modeling of the sections during the Quaternary, under the effect of climate alternations, also creates the conditions for the genesis and evolution of soil cover to it associated. Currently, each pedological system shows, besides the effects of this history of evolution, transformations produced by use and occupancy of these strands by man.